“Who Is That Teacher I See, Staring Straight Back At Me?”: Teachers’ Reflections on Their Engagement in Communities of Practice and Learning Spaces During the Pandemic - Junifer Abatayo (Gulf Education and Social Policy Review)
When COVID-19 hits the world, education as a sphere of learning breaks through doorways to explore opportunities for how teachers engage in professional development communities. Exploring Parker Palmer’s The Courage To Teach, and the notion of undivided life, teachers’ reflective practices mirror the utmost goal of emergency remote teaching and their professional development, specifically in the Gulf region. To support this pedagogical approach highlighting the undivided life, teachers reflect through communities of practice (CoP) on how their engagement can help bridge the gap in enhancing the education system, professional development, and teaching in higher education. This paper investigates the practicality and usefulness of Palmer’s context of undivided life in uncovering teachers’ lives through understanding their “own” engagement in different CoP. Ultimately, the investigation espouses relevant findings relating to how teachers adapt to the changing needs of professional learning communities to cope with the demands of time through reflecting on their professional identities, collaborative practices, and the importance of community belongingness. The stories documented in this paper through the in-depth interview (IDI) hope to provide meaningful perspectives on guided principles of CoP as teachers engage, collaborate, and reflect on the divided–undivided lives during the pandemic. Perspectives and views that have impact on positive education are also considered in this study to support teachers in building deeper understanding of their own construct of resilience. Thus, adding more foci in transforming positive psychology in developing teachers’ professional development during the pandemic.